Highly efficient recovery of biophenols onto graphene oxide nanosheets: Valorisation of a biomass - Ilbay, Zeynep; Hasimoglu, Aydin; Ozdemir, Oguz Kaan; Ates, Fadime; Sahin, Selin (ELSEVIER SCIENCE BV, 2017)
In this study, graphene oxide (GO) nanosheets were evaluated for the recovery of biophenols from an agricultural biomass, olive leaf. Modified Hummer's method was used to synthesize GO by natural oxidation of graphite. The adsorbent was characterized by several novel analysis methods such as Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and X-ray diffraction (XRD). On the other hand, optimization of the adsorption process was applied utilizing multivariate statistic technique such as Response Surface Methodology (RSM) in order to consider any possible interaction between variables with less number of experiments as well as to model a response affected by several variables. The outcome of the present study indicates that the optimum conditions for the adsorption of were 4.57/10 of pH together with 24.62/30 degrees C of temperature and 3 mg of GO to achieve the maximum yields of each dependent variable such as total biophenol content (TBC) and the most prevalent compound, oleuropein (OC). The verification of the calculated models was held by several error function analysis. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Biomass valorization; Graphene oxide; Oleuropein; Adsorption; Optimization; OLEA-EUROPAEA L.; PHENOLIC-COMPOUNDS PRESENT; AQUEOUS-SOLUTIONS; ACTIVATED CARBON; DYE ADSORPTION; PURIFICATION; EXTRACTION; ANTIOXIDANT; LEAVES; Chemistry; Physics